2016
DOI: 10.1101/036384
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rare loss-of-function variants inKMT2Fare associated with schizophrenia and developmental disorders

Abstract: Rare% loss)of)function% variants% in% KMT2F% are% associated% with%schizophrenia%and%developmental%disorders%

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Identification of an additional potentially functional de novo synonymous mutation in this gene and the accumulating evidence for involvement of the chromatin regulation pathway in neuropsychiatric diseases, including ASD and SCZ, further supports that SETD1A is a genuine susceptibility gene for SCZ. Notably, strong association of LOF mutations in SETD1A (also known as KMT2F ) with SCZ was confirmed by a recent large-scale study examining several tens of thousands of WES data (Singh et al, 2016). …”
Section: Discussionmentioning
confidence: 79%
“…Identification of an additional potentially functional de novo synonymous mutation in this gene and the accumulating evidence for involvement of the chromatin regulation pathway in neuropsychiatric diseases, including ASD and SCZ, further supports that SETD1A is a genuine susceptibility gene for SCZ. Notably, strong association of LOF mutations in SETD1A (also known as KMT2F ) with SCZ was confirmed by a recent large-scale study examining several tens of thousands of WES data (Singh et al, 2016). …”
Section: Discussionmentioning
confidence: 79%
“…A risk score from exome variants could be combined with a polygenic risk score from common SNPs. It could also be combined with risk scores derived from identified rare variants which have been shown to have a major effect on risk, such as specific copy number variants and gene mutations (Raychaudhuri et al, 2010;Singh et al, 2016). A recent study of autism has demonstrated that in subjects who possess rare variants having major effects on risk for autism, common variants can increase this risk further (Weiner et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…81 Most recently, a combined analysis of 4264 cases, 9343 controls, and 1077 trios (which included the exomes sequenced in the two 2014 papers) reported a significant excess of very rare (including de novo) gene-disrupting variants in the SETD1A (SET domain containing 1A) gene in schizophrenia patients, finding 10 in 5341 unrelated cases (0.19%) and none in 9343 controls. 3 This represents the first time that NGS has shown a statistically significant association between schizophrenia and a single candidate gene. SETD1A is involved in histone methylation and the association with schizophrenia further substantiates the report that common risk variants for psychiatric disorders may ag-gregate on histone methylation pathways.…”
Section: Schizophreniamentioning
confidence: 91%
“…gene in amyotrophic lateral sclerosis (ALS). 2 Strikingly, such analyses allow a direct investigation of the underlying architecture of disease, and the cases of ALS, schizophrenia, 3 and unpublished studies of epilepsy and other conditions show that it is the very rarest variants that carry the strongest signal of risk. These results illustrate two critical features about complex human diseases.…”
Section: S T a T E O F T H E A R Tmentioning
confidence: 99%